Pengaruh Kesadaran Merek dan Kualitas Pelayanan Terhadap Minat Beli Produk Kopi Kenangan - Nadia Priskila Angelin; Anjar Dwi Astono (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this research, to know and analyze the influence of brand awareness and service quality on the interest of buying Kopi Kenangan. This research uses a quantitative method with purposive sampling with the criteria that consumers have bought and tried Kopi Kenangan products and are at least 17 years old. The questionnaire survey was distributed via google form to 150 respondents which was then processed using SPSS version 25.0. Based on the results of hypothesis testing (t test) that brand awareness has a significant effect on buying interest, service quality has a significant effect on buying interest and brand awareness and service quality simultaneously have a significant effect on buying interest.